Mitochondrial Dynamics Imbalance: A Strategy for Promoting Viral Infection - Ren, Zhihua; Zhang, Xiaojie; Ding, Ting; Zhong, Zhijun; Hu, Hui; Xu, Zhiwen; Deng, Junliang (Frontiers in Microbiology, 2020)
Mitochondria are highly dynamic organelles that maintain the dynamic balance of split-fusion via kinetic proteins. This maintains the stability of their morphological functions. This dynamic balance is highly susceptible to various stress environments, including viral infection. After viral infection, the dynamic balance of the host cell mitochondria is disturbed, affecting the processes of energy generation, metabolism, and innate immunity. This creates an intracellular environment that is conducive to viral proliferation, and begins the process of its own infection and causes further damage to the body. Herein, we discuss the mechanism of the virus-induced mitochondrial dynamics imbalance and its subsequent effects on the body, which will help to improve our understanding of the relationship between mitochondrial dynamics and viral infection and its importance.